Transformasi Mutagenesis Terarah Gen Pengkode UGTs Upstream-site yang Dimediasi Agrobacterium tumefaciens Strain LBA4404 Berbasis CRISPR/Cas9 Pada Tanaman Padi - Dewi, Tifanny Achita (Fakultas Pertanian, 2026)
Sakuranetin is a phytoalexin compound produced in response to pathogen attack and environmental stress. Sakuranetin also has other functions, such as antimicrobial, antiviral, antioxidant, antidiabetic, and anticancer properties. Sakuranetin is synthesized through the glycosylation of naringenin, the primary precursor of the sakuranetin biosynthesis pathway. Naringenin is readily converted by UGTs (UDP-Glucosyltransferase) enzymes into other derivative compounds. Based on this, mutations in UGTs are important to change the transcriptional regulation of these genes and increase the activity of the enzyme that catalyzes the glycosylation of naringenin to sakuranetin, thereby strengthening the plant's defense mechanism effectively. This study aims to determine the efficiency of CRISPR/Cas9 sg-RNA UGTs-based mutagenesis transformation, as well as to analyze the regeneration rate of transformants in several local rice varieties. This research was conducted at the Agrobiotechnology Laboratory, Faculty of Agriculture, University of Jember. The research results were analyzed using simple descriptive statistics to obtain an overview of the regeneration ability of transformants and the efficiency of transformation into the rice plant genome. The results of this study showed a transformation efficiency of 0.2% in the Pandan Wangi variety and 0.1% in the Ketan Hitam and Pendok varieties. Two putative transformant rice plants were obtained in the Pandan Wangi variety and one plant in the Ketan Hitam and Pendok varieties. Differences in transformation efficiency were influenced by the response of the plant genotype to the infection process and T-DNA transfer by A. tumefaciens.
FINALISASI oleh Agus 2026 Juni 23
Keywords: UDP-Glucosyltransferase; CRISPR/Cas9; Sakuranetin; Tanaman Padi